Routledge international handbook of the sociology of art and culture - Hanquinet, Laurie; Savage, Michael (Routledge, 2015)
pt. 1. Bourdieu's legacy and new perspectives for the sociology of art and culture -- pt. 2. The fabric of aesthetics -- pt. 3. The complexity of cultural classifications
Includes bibliographical references and index
Keywords: Electronic books; Aufsatzsammlung; Kulturkontakt; Gesellschaft; Kultur; Künste